MICROBIAL SIDE - CHAIN DEGRADATIONOF PROGESTERONE II. APPLICATIONOF DIFFERENT TECHNIQUESFOR PROGESTERONE CONVERSIONBYFUSARIUMDIMERIUM - Adham, Nehad Z; Tayeb, Osama M El -; Hashem, Abdel - Gawad M; Refai, Heba El -; Sallam, Lotfy A (Biological Sciences - PJSIR, 2004)
A local isolate of Fusarium dimerium, firstly reported to be able to degrade progesterone side chain to give certain C-19 androgenes derivatives, proved to perform this important conversion more efficiently adopting the cell immobilization technique. Thus, relatively more amounts of Androst - 4 - ene - 3, 17 - dione (AD), Testololactone (TL) (major products) as well as, Testosterone (T), Androsta - 1,4 - diene 3, 17 - dione (ADD) (minor products) were recorded after 72 h using 2 % Ca - alginate immobilized fungal cells. Relatively lower bioconversion rates were achieved when the bioconversion process was carried out in top - laboratory fermentor using free cells of the promising